cognitive complaints in schizophrenia: characteristics and relationship with insight - M. Bouhamed; S. Hentati; A. Bouaziz; A. Guermazi; R. Sallemi; J. Masmoudi (European Psychiatry, 2022)
Introduction Patients with schizophrenia suffer from cognitive difficulties expressed in the form of complaints as well as poor insight. The interaction of these two factors makes the management of these patients more difficult.